2004
DOI: 10.1539/joh.46.281
|View full text |Cite
|
Sign up to set email alerts
|

Serum Oxidant and Antioxidant Levels in Diesel Exposed Toll Collectors

Abstract: Serum Oxidant and Antioxidant Levels in Diesel Exposed Toll Collectors: Peri ARBAK, et al. Department of Chest Diseases, Abant Izzet Baysal University, Duzce School of Medicine, Turkey-It has been suggested that exposure to diesel exhaust may lead to adverse effects due to the generation of oxidants. To evaluate the end products of oxidative stress in DE exposure, toll collectors who are considered a high risk group in regard to occupational toxins were compared to controls who had office-based occupations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(42 reference statements)
0
12
1
Order By: Relevance
“…One possible reason for this alteration appears to be exposure to toxic substances in the environment, and notably ambient air pollution [54][55][56]. It has indeed been demonstrated that professions exposed to exhaust, such as toll collectors working on expressways, more frequently develop sperm abnormalities [16,57].…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 99%
See 2 more Smart Citations
“…One possible reason for this alteration appears to be exposure to toxic substances in the environment, and notably ambient air pollution [54][55][56]. It has indeed been demonstrated that professions exposed to exhaust, such as toll collectors working on expressways, more frequently develop sperm abnormalities [16,57].…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 99%
“…They can be transformed by CYP450 dihydro-dehydrogenase, which produces quinone redox, catalyzing electron transfer reactions and thus stimulating ROS production [93,[16][17][18].…”
Section: Induction Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with those of Kü nzli et al, 14 who demonstrated an association between air pollution and IMT. In the same area of Turkey (Kaynaslı, Golyaka-Duzce), Arbak et al 15 reported marked air pollution, of which exhaust particles were an important part. 15 Increased blood glucose, total cholesterol, lowdensity lipoprotein cholesterol, decreased highdensity lipoprotein cholesterol, and increased body mass index are associated with increased IMT.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies focused on manual tollbooth collectors reported acute irritative symptoms due to nasal and throat inflammation, nausea, headache and lower peak expiratory flow rates 7,8) .…”
Section: Introductionmentioning
confidence: 99%